How Distortion on the Electric Power Market Can Lead to Stagflation - KriÅ¾aniÄ, France; Mencinger, JoÅ¾e; Oplotnik, Zan (International Journal of Energy Economics and Policy, 2018)
At the time of the possible closure of the significant Slovenian classical electricity production in the Å oÅ¡tanj Thermal Power Plant and related Velenje Coal Mine, as well as the termination of the subsidies of cost-inefficient electric power production in EU member states, electricity prices in Slovenia for one third of its supply would rise to a level set to cover the cost of its production with a conventional gas-steam turbine. Calculated for the price of electricity produced in the Å oÅ¡tanj Thermal Power Plant, this means an average price increase of 39 â‚¬/MWh. Higher prices of electricity would affect the performance and capacity of the Slovenian economy while bringing a reduction to real household income along with annual drops in Slovenian GDP of 0.4%, Slovenia would stand to lose around 2,700 jobs, and the consumer price level would rise by 0.4%. Keywords: Electricity Power Market, Electricity Supply and Demand, Energy and the Economy JEL Classifications: D40, L94, Q3, Q43 DOI: https://doi.org/10.32479/ijeep.7112